Functionalisation of Ti6Al4V components fabricated using selective laser melting with a bioactive compound - Vaithilingam, Jayasheelan; Kilsby, Samuel; Goodridge, Ruth D.; Christie, Steven D.R.; Edmondson, Steve; Hague, Richard J.M. (Elsevier, 2015)
Surface modification of an implant with a biomolecule is used to improve its biocompatibility and to reduce post-implant complications. In this study, a novel approach has been used to functionalise phosphonic acid monolayers with a drug. Ti6Al4V components fabricated using selective laser melting (SLM) were functionalised with Paracetamol (a pharmaceutically relevant biomolecule) using phosphonic acid based self-assembled monolayers (SAMs). The attachment, stability of the monolayers on the SLM fabricated surface and functionalisation of SAMs with Paracetamol were studied using X-ray photoelectron spectroscopy (XPS) and surface wettability measurements. The obtained results confirmed that SAMs were stable on the Ti6Al4V surface for over four weeks and then began to desorb from the surface. The reaction used to functionalise the phosphonic acid monolayers with Paracetamol was noted to be successful. Thus, the proposed method has the potential to immobilise drugs/proteins to SAM coated surfaces and improve their biocompatibility and reduce post-implant complications.